COMPREHENSIVE STUDY ANALYSIS OF NOVEL MAPPING MULTIPLEXING (NMM) TECHNIQUE FOR LONG HAUL OPTICAL FIBER TRANSMISSION SYSTEMS - Saqlain, Muhammad; Illahi, Usman; Iqbal, Javed; Ehsan, Ali (European Scientific Journal, ESJ, 2013)
A new multiplexing technique based on mapping method called Novel Mapping Multiplexing (NMM) is proposed and well demonstrated. It is reported that spectral width occupied by 40 Gb/s NMM is 40 GHz with spectral efficiency of 1bit/sec/Hz that shows a clear advantage over the conventional NRZ-OOK and RZ-OOK with same data rate of 40Gbits/sec having spectral efficiency of 0.5bit/sec/Hz and 0.25bit/sec/Hz respectively. This technique features better chromatic dispersion (CD) tolerance and Q-Factor because of its narrow spectral width.